LESSONS LEARNED FROM THE 2010 CANTERBURY EARTHQUAKE AND AFTERSHOCKS, NEW ZEALAND - Sugeng Wijanto; C.W.K. Hyland (Institut Teknologi Sepuluh Nopember, 2011)
A moderate M7.1 earthquake hit Canterbury on Saturday, 4 September, 2010 at 04:35:46 a.m. New Zealand time (GMT +12). It was expected to be the most damaging ground shake since the 1931 magnitude 7.8 Hawke's Bay earthquake. The epicentre was located approximately 45 km west of Christchurch, in a rural area at a depth of 10 km. There were followed by more than thousand aftershocks had been measured. An aftershock M6.3 was recorded at 12:51 pm on Tuesday, 22 February 2011. The epicentre of the aftershock was approximately 10 km south-east of the Christchurch Central Business District (CBD), near Lyttelton, at a similar depth to the initial earthquake and caused much more severe damage to CBD and residential areas nearby. Lessons learned from the Canterbury earthquake and its aftershocks are a timely reminder to Indonesian structural engineers of a number of things with respect to seismic design, construction practices and post disaster evaluation. These include: The importance of implementing the latest seismic loadings and design technology into new and existing structures without undue delay; The need to maintain effective Building Code enforcement and post-earthquake audit process, including the keeping of publicly transparent compliance records; The important role of the design engineer in observing and auditing the interpretation and implementation of the design; Vigilance to prevent improper substitution of materials and ill-considered design changes; The importance of ongoing continuing professional development and education for design, construction and building code enforcement officials. This paper also discusses the need of having a guide for conducting post-earthquake structural repairs as including a quick way to identify appropriate repair strategies.